Analysis of the Contribution of Rhythmic Movement Ability Assessment Components in a Virtual Gymnastics Competition - Firdaus Hendry Prabowo Yudho; Aisya Kemala; Aris Mulyono; Maria Herlinda Dos Santos; Muhammad Iqbal Hasanuddin; Dicky Reva Apriana Sanga Dwi (JUARA : Jurnal Olahraga, 2022)
The study aimed to investigate the relationship and influence between following movement (FM) and Movement Technic (MT) variables on general performance (GP) performances conducted by participants in virtual gymnastics competitions (n=361) organized by the Ministry of Youth and Sports during the pandemic in 2020. Research is conducted through quantitative approaches, descriptive analysis and linear regression hypothesis tests to determine the relationships and influences between these variables. Statistical analysis conducted resulted in significant relationship findings and forces between independent FM, and MT, variables on GP dependent variables. The study concluded a strong p.977 positive relationship between variables in the influence of ability to follow movements on general appearance and a negative .987 negative relationship between motion techniques and public appearance in assessing virtual exercise competition.